Perceptions and reflections of primary healthcare professionals on mental health services in Makhanda - Piliso, Zandisiwe (Rhodes University, Faculty of Humanities, Department of Psychology)
Primary mental healthcare in South Africa is still in its early stages, despite policies that have been developed, such as the National Mental Health Framework Policy. Provinces such as the Eastern Cape are far behind development, which can be attributed to limited resources. The scarcity has been noted in the literature, but not extensively. Literature concentrated on healthcare professionals' perspectives towards primary health greatly narrow, particularly in the Makhanda area. With the integration of primary mental health services, healthcare workers' viewpoints have impacted on service delivery. This study aims to add knowledge and explore the perspectives of healthcare professionals on primary mental healthcare in Makhanda. The ecological systems theory was used as a theoretical framework for the study. Thematic analysis was used to examine the healthcare professionals' insights and to extract meaning for the participants involved in the study. Thirteen participants were used, using purposive sampling in four primary healthcare settings. Data were collected using semi-structured and one-on-one interviews. The study revealed three themes including, (i) Scarcity of Mental Health Services, (ii) Mental Health Literacy, (iii) Barriers to the Provision and Use of Physical and Mental Health Services. The findings suggest that there are limited mental health care services in primary care and that there is a gap between service provision and physical and mental healthcare. The data also revealed that mental health literacy is limited, which links to the stigma around mental illness. Furthermore, evidence points out that more mental health education, human resources and training of healthcare professionals would further improve the mental health services in the Makhanda area. In addition, there are barriers to the provision of not only primary mental health care but healthcare, as well as a lack of medical equipment, human resources, and structural space that make it difficult for healthcare professionals to perform their jobs and affect clinic functioning, at times. Another barrier is that the perception of mental health service provision is simultaneously viewed in a positive and negative light and mainly received negatively by service users. In conclusion, healthcare professionals experience a deficiency of resources and a limited provision of mental healthcare, which highlights the lack of implementation of policies that have developed nationally and globally.
Keywords: Primary care (Medicine); Mental health services -- South Africa -- Makhanda; Medical personnel; Ecological Systems Theory; Mental health personnel -- South Africa -- Makhanda